(untitled) (Bangladesh Pharmaceutical Journal, 2025)
Araucaria heterophylla (Salisb.) Franco (Araucariaceae) is found all over the country mostly for ornamental purposes. It is widely used as an antiseptic, emollient and in the treatment of ulcers, rheumatism, toothache as well as respiratory infection. The present study was aimed to investigate GCMS analysis, in vitro antioxidant activity and antimicrobial activity of ethanolic leaf extract of A. heterophylla (Salisb.) Franco (EAH). EAH was investigated by the GC-MS electron impact ionization (EI) method on a GC-2010 Plus gas chromatograph coupled to a GCMS-QP2010 Ultra mass spectrometer. In vitro antioxidant activity was evaluated by DPPH free radical scavenging assay along with the determination of total phenolic content (TPC) and total flavonoid content (TFC). Antimicrobial activity screening was performed by agar disc diffusion method against two Gram-positive (Staphylococcus aureus and Bacillus megaterium) and two Gram-negative bacteria (Escherichia coli and Salmonella typhi) as well as a fungal strain (Trichoderma harzianum). Nine phytoconstituents were identified with the maximum concentration of 2,2,4-Trimethyl-3-pentanol. TPC of EAH was determined at 193.46 ± 4.93 mg GAE/g, whereas TFC was found at 560.16 ± 64.97 mg QE/g. Percentage (%) DPPH free radical scavenging by EAH was found in a dose-dependent manner. The IC50 value was calculated by regression analysis, and the value of ascorbic acid and EAH was found at 8.05 and 33.17 μg/ml, respectively. Antimicrobial activity was expressed in terms of the zone of inhibition which was found against S. aureus, B. megaterium, E. Coli, S. typhi and T. harzianum 29.87 ± 1.86, 20.60 ± 1.93, 37.63 ± 3.56, 20.43 ± 2.38, 13.20 ± 1.71 mm, respectively. The findings indicate this plant could be a potential source for drug development. Bangladesh Pharmaceutical Journal 28(2): 175-183, 2025 (July